The Oxidative Injury of Extracellular Hemoglobin Is Associated With Reactive Oxygen Species Generation of Grass Carp (Ctenopharyngodon idella) - Qin, Zhendong; Yang, Minxuan; Lu, Zhijie; Babu, V. Sarath; Li, Yanan; Shi, Fei; Zhan, Fanbin; Liu, Chun; Li, Jun; Lin, Li (Frontiers in Immunology, 2022)
Intravascular hemolysis is a fundamental feature of hemorrhagic venereal infection or tissue and releases the endogenous damage-associated molecular pattern hemoglobin (Hb) into the plasma or tissues, which results in systemic inflammation, vasomotor dysfunction, thrombophilia, and proliferative vasculopathy. However, how the cytotoxic Hb affects the tissues of grass carp remains unclear. Here, we established a hemolysis model in grass carp by injecting phenylhydrazine (PHZ). The data revealed that the PHZ-induced hemolysis increased the content of Hb and activated the antioxidant system in plasma. The histopathology analysis data showed that the PHZ-induced hemolysis increased the accumulation of Hb and iron both in the head and middle kidney. The results of quantitative real-time PCR (qRT-PCR) detection suggested that the hemolysis upregulated the expressions of iron metabolism-related genes. In addition, the immunofluorescence and immunohistochemistry data revealed that the hemolysis caused an obvious deposition of collagen fiber, malondialdehyde (MDA), and 4-hydroxynonenal (4-HNE) accumulation and increased the content of oxidative-related enzymes such as β-galactosidase (β-GAL), lipid peroxide (LPO), and MDA in both the head and middle kidney. Furthermore, the PHZ-induced hemolysis significantly increased the production of reactive oxygen species (ROS), which resulted in apoptosis and modulated the expressions of cytokine-related genes. Taken together, excess of Hb released from hemolysis caused tissue oxidative damage, which may be associated with ROS and inflammation generation.